f(x)=4-x^2 simplify completly. Use difference quotient.

1 answer

( x - 2 ) ( x + 2 ) =

x ^ 2 - 2 x + 2 x - 4 =

x ^ 2 - 4 =

- ( x ^ 2 - 4 ) =

4 - x ^ 2

So :

4 - x ^ 2 = - ( x - 2 ) ( x + 2 )
Similar Questions
    1. answers icon 1 answer
  1. 8th grade Quotient Rule of Exponents Quick Check ConnexusSimplify this expression using the Quotient Rule of Integer Exponents:
    1. answers icon 24 answers
  2. The expression 12÷d is given. Translate the expression into words.(1 point)Responses the difference of a number d and 12 the
    1. answers icon 1 answer
  3. Quotient Rule of Exponents Quick CheckMath 8 Q1 (Pre-Algebra) / Exponent Rules Simplify this expression using the Quotient Rule
    1. answers icon 1 answer
more similar questions